The comparative analysis of the fields of scientific researches in the domestic and foreign theses on psychiatry (1992-2015) - V. I. Evdokimov; V. K. Shamrey; E. I. Chekhlaty; S. A. Semin (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The carried-out retrieval revealed 2326 theses in 14.01.06 (14.00.18) «Psychiatry». In 1992-2015 about 97±6 theses were presented annually to dissertation councils of Russia. Doctor’s degree works there were 16.9%, candidate - 81.3%. Works on psychiatry made 2.5% of total medical ones in Russia. Retrieval on 01.05.2016 allowed to find 53,694 responses to theses on psychiatry in the ProQuest Dissertations & Theses Database. The number of annually published foreign theses on psychiatry constituted 2270±160. Theses published in English was 98.1% among the aspired for academic degree, 79.5% - for doctor of philosophy (Ph.D.). Structures of bases of domestic and foreign doctoral dissertations differed slightly. In russian dissertation works were significantly more often researched the subjects of military psychiatry, the issues of clinic, diagnostic and treatment of mental disorders and rehabilitaiton of mentally ill. In the foreign pool there wer more works dedicated to child psychiatry and psychosomatic disorders.